2018
DOI: 10.47197/retos.v0i35.64083
|View full text |Cite
|
Sign up to set email alerts
|

Actividad física, condición física y autoconcepto en escolares de 8 a 12 años (Physical activity, physical fitness and self-concept in schoolchildren aged between 8 to 12 years old)

Abstract: Este artículo analizó la relación entre actividad física, condición física y autoconcepto. Un total de 103 escolares (8-12 años) participaron en la evaluación de dichas variables. La condición física se valoró mediante diversas pruebas de la Batería ALPHA-Fitness, el nivel de actividad física se calculó a través del cuestionario PACE y el autoconcepto se midió utilizando la Escala de Autoconcepto de Piers-Harris. Las pruebas estadísticas fueron: T-student, U de Mann-Whitney y Krustal-Wallis. Aquellos físicamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
3
4
0
2
Order By: Relevance
“…Interestingly, better results in control group when applying physical fitness motor tests were also found in previous investigations ( Rosa et al, 2019 ; Carriedo et al, 2022 ). There the control group students got better quantitative results in standing long jump, speed-agility and cardiorespiratory endurance tests as it happens in our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, better results in control group when applying physical fitness motor tests were also found in previous investigations ( Rosa et al, 2019 ; Carriedo et al, 2022 ). There the control group students got better quantitative results in standing long jump, speed-agility and cardiorespiratory endurance tests as it happens in our study.…”
Section: Discussionsupporting
confidence: 85%
“…The consistency of our results with the findings of Rosa et al (2019) led us to reconsider and relativize our first hypothesis to explain them. Initially, the non-significant results in the experimental group were attributed to the public health crisis caused by COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 80%
“…As for the A+ group, they are those who carry out the most physical activity (intense, moderate, and low), and also stand out as those who dedicate the most minutes per day to intense, moderate, and walking activities, along the same lines as the findings of the works of Dieppa et al [ 48 ] and Contreras et al [ 49 ]. Notably for this group, which also reported higher levels of physical self-concept than a pre-pandemic study, a positive correlation was found between this aspect and higher levels of physical activity [ 28 ] and along the same lines as concluded by Guillamón, García, and Carrillo [ 50 ]. Finally, group A−, stands out for being the least active (intense, moderate, and low), this group is the one in which the highest number of individuals did not perform any physical activity in the last 7 days, as well as the group that walked the least minutes and days per week, which may be associated with the scenario of the COVID-19 pandemic during the year 2020 and the social isolation and/or quarantine that had a significant impact on the levels of physical activity and exercise [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 68%
“…Adolescence is a decisive age period for the generation and consolidation of a healthy lifestyle, which inevitably needs a PA practice on a regular basis [19], being aware that positive habits consolidated at an early age have an impact on the adulthood [20]. Some of the benefits of PA practice include the prevention or improvement in certain diseases such as cardiovascular diseases, the improvement of physical condition [21], benefits at the psychosocial level such as the promotion of self-esteem, reduction of depression and stress [22], cognitive development [23,24], socialization and academic performance [25,26]. However, at present, PA practice does not comply with the recommendations established for adolescents [27], due to, among other reasons, the increasing use of new technologies and display devices [28,29].…”
Section: Introductionmentioning
confidence: 99%